2004
DOI: 10.1016/j.stam.2003.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Joint strength and interfacial microstructure between Sn–Ag–Cu and Sn–Zn–Bi solders and Cu substrate

Abstract: In the present research, in order to fundamentally investigate the strength and interfacial microstructure of the joints between Sn-3.5Ag-0.7Cu (SAC) and Sn-8Zn-3Bi (SZB) solders and Cu, examinations using the standardized solder joint specimen for measuring the shear strength were performed. The effects of the addition of Ag, Bi and Pb to the solders, which are the ingredients of possible lead plating materials of quad plat package, solder layer thickness and aging treatments ranging from 358 to 423 K were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…The measured strength of joints is the tensile shear strength due to the applied shear stress during the tensile testing, because two Cu wires were not coaxial. It was estimated by dividing the highest failure force value by the bonding area [24,50,51], r = F max /A (N/mm 2 or MPa). The fracture area of samples was difficult to measure Sintered paste with different Ag NW volume additions f 0 vol%, g 10 vol% and i 30 vol% after sintering at 150°C for 1 h. Inset low magnification image h and j are corresponding to Ag NP/10NW and Ag NP/30NW pastes due to the unsymmetrical geometry of fracture region.…”
Section: Resultsmentioning
confidence: 99%
“…The measured strength of joints is the tensile shear strength due to the applied shear stress during the tensile testing, because two Cu wires were not coaxial. It was estimated by dividing the highest failure force value by the bonding area [24,50,51], r = F max /A (N/mm 2 or MPa). The fracture area of samples was difficult to measure Sintered paste with different Ag NW volume additions f 0 vol%, g 10 vol% and i 30 vol% after sintering at 150°C for 1 h. Inset low magnification image h and j are corresponding to Ag NP/10NW and Ag NP/30NW pastes due to the unsymmetrical geometry of fracture region.…”
Section: Resultsmentioning
confidence: 99%
“…So, the strength of the solder joints is important for this role [4]. There are not many studies reported on the mechanical properties of the joints by Sn-Zn solders [5,6,7], and a few stress-strain curves have been reported for the solders [5]. The mechanical properties of the substrate/solder joint are greatly influenced by the interface reaction products between them.…”
Section: Introductionmentioning
confidence: 99%
“…However, the tendency of oxidation, and poor wetting ability of this alloy system confine its application [5,6]. In recent years, to overcome the shortfall of Sn-9Zn, some authors have tried to add a third element, such as In [7], Bi [8][9][10], Al [11][12][13][14][15], Ag [16][17][18], and Ce/La [19][20][21] to the Sn-Zn binary system to improve the melting temperature, wettability, oxidation resistance, corrosion, and mechanical properties of the alloy.…”
Section: Introductionmentioning
confidence: 99%